Pluralism Theology of Nurcholis Madjid - Andi Ahmad Zahri Nafis; Barsihannor Barsihannor; Indo Santalia (AL-MUTSLA, 2023)
Pluralism is an understanding of mutual respect and understanding of differences in people's lives. Nurcholish Madjid's thoughts are considered relevant for discussion. As a figure to be reckoned with in Indonesia, his existence is considered to represent the rise of reform thinking in the archipelago. His thoughts on pluralism are considered a necessity associated with the condition of religious communities in Indonesia. The statement is based on the Indonesian population's condition of religious pluralism. If the pluralism of religions adhered to is not glued together with a pluralistic perspective, then the plurality of religions has the potential to trigger conflict. This research aims to find out the thoughts of Kalam Nurcholish Madjid on Pluralism. The method used is literature study by taking references from various sources such as printed and digital books, as well as research-related journals. The results of the study show that there are three approaches used by Nurcholis Madjid in formulating the concept of Pluralism, namely first, the Tawheed approach, namely the return of human dignity and status back to its position as a creature of Allah. Humans look up "up" only to God, to fellow human beings must look in a series of equality. Second, the Philological Approach, namely the redefinition of the meaning of Islam or more precisely the expansion of the definition of Islam as an attitude of surrender, submission, and obedience to God Almighty. The third is the Historical Approach, which is the value or spirit contained in that history. In this case, every adherent of religion needs to take as an example the values of openness of the people of Medina at that time, not to take the form of the government of the Prophet Muhammad in Medina to be applied today.